Biomechanical Evaluation of Transpedicular Nucleotomy With Intact Annulus Fibrosus. Issue 4 (15th February 2017) - Russo, Fabrizio; Hartman, Robert A.; Bell, Kevin M.; Vo, Nam; Sowa, Gwendolyn A.; Kang, James D.; Vadalà, Gianluca; Denaro, Vincenzo
Abstract : Study Design: Biomechanical testing of partially nucleotomized ovine cadaveric spines. Objective: To explore how the nucleus pulposus (NP) affects the biomechanical behavior of the intervertebral disc (IVD) by performing a partial nucleotomy via the transpedicular approach. Summary of Background Data: Mechanical loading represents a crucial part of IVD homeostasis. However, traditional regenerative strategies require violation of the annulus fibrosus (AF) resulting in significant alteration of joint mechanics. The transpedicular nucleotomy represents a suitable method to create a cavity into the NP, as a model to study IVD regeneration with intact AF. Methods: A total of 30 ovine-lumbar- functional spinal units (FSUs) (L1-L6) randomly assigned to 5 groups: control; transpedicular tunnel (TT); TT + polymethylmethacrylate (PMMA) to repair the bone tunnel; nucleotomy; nucleotomy + PMMA. Flexion/extension, lateral-bending, and axial-rotation were evaluated under adaptive displacement control. Axial compression was applied for 15 cycles of preconditioning followed by 1 hour of constant compression. Viscoelastic behavior was modeled and parameterized. Results: TT has minimal effects on rotational biomechanics. The nucleotomy increases ROM and neutral zone (NZ) displacement width whereas decreasing NZ stiffness. TT + PMMA has small effects in terms of ROM. Nucleotomy + PMMA brings ROM back to the control, increases NZ stiffness, and decreases NZ displacement width. The nucleotomy tends to increase the rate of early creep. TT reduces early and late damping. The use of PMMA increased late elastic stiffness (S2 ) and reduced viscous damping (η2 ) culminating in faster resolution of creep. Conclusion: Biomechanical properties of NP are crucial for IVD repair. This study demonstrated that TT does not affect rotational stability whereas partial nucleotomy with intact AF induce rotational instability, highlighting the central role of NP in early stages of IDD. Therefore, this model represents a successful platform to validate and optimize disc regeneration strategies. Level of Evidence: N/A